The Relationship Between Self-Concept and Decision Making in High School Alumni Undergoing a Gap Year - Nikerson, Stefanus Anggoro; Sarajar, Dewita Karema (Department of Guidance and Counseling, FIP, Undiksha, 2024)
Gap year is a period of time used by high school alumni to prepare themselves for continuing their education at university level. The competition that is not easy to get into college makes a gap year an option for preparing yourself. This research aims to analyze the relationship between self-concept and decision making in high school alumni who are undergoing a gap year. The research method used is quantitative with a Pearson's Product Moment correlational design. This research involved 103 high school alumni from all regions in Indonesia who underwent a gap year using the snowball sampling technique. Data collection was carried out using a psychological scale according to the variables which was then distributed online using a Google form. Data were analyzed using product moment correlation analysis by Karl Pearson. The results of this study show that the variables of self-concept and decision making are positively correlated with a weak level of significance with value (r = 0.211 and sig. = 0.016). It can be concluded that self-concept is one of the factors that can improve the decision-making ability of high school alumni who are undergoing a gap year. The latest information in this research has implications for the formation of good concepts by high school alumni to be more optimistic in making decisions about undergoing a gap year.